The Magnetospheric Cusps: Structure and Dynamics - Fritz, Theodore A.; Fung, Shing F.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
This collection of papers will address the question "What is the Magnetospheric Cusp?" and what is its role in the coupling of the solar wind to the magnetosphere as well as its role in the processes of particle transport and energization within the magnetosphere. The cusps have traditionally been described as narrow funnel-shaped regions that provide a focus of the Chapman-Ferraro currents that flow on the magnetopause, a boundary between the cavity dominated by the geomagnetic field (i.e., the magnetosphere) and the external region of the interplanetary medium. Measurements from a number of recent satellite programs have shown that the cusp is not confined to a narrow region near local noon but appears to encompass a large portion of the dayside high-latitude magnetosphere and it appears that the cusp is a major source region for the production of energetic charged particles for the magnetosphere. Audience: This book will be of interest to space science research organizations in governments and industries, the community of Space Physics scientists and university departments of physics, astronomy, space physics, and geophysics.
Preface -- Cluster Observations of the Cusp: Magnetic Structure and Dynamics -- Magion-4 High-Altitude Cusp Study -- High-Altitude Cusp: The Extremely Dynamic Region in Geospace -- Magnetosheath Interaction with the high Latitude Magnetopause -- Cluster Observes the High-Altitude Cusp Region -- Low-Frequency Plasma Waves in the Outer Polar Cusp: A Review of Observations from Prognoz 8, Interball 1, Magion 4, and Cluster -- Multiple Flux Rope Events at the High-Latitude Magnetopause: Cluster/Rapid Observation on 26 January, 2001 -- Energetic Electrons as a Field Line Topology Tracer in the High Latitude Boundary/Cusp Region: Cluster Rapid Observations -- Energetic Particles Observed in the Cusp Region During a Storm Recovery Phase -- Coupling the Solar-Wind/IMF to the Ionosphere Through the high Latitude Cusps -- Spatial and Temporal Cusp Structures Observed by Multiple Spacecraft and Ground Based Observations -- Observations of a Unique Cusp Signature at Low and Mid Altitudes -- Cusp Modeling and Observations at Low Altitude -- Simulation Studies of High-Latitude Magnetospheric Boundary Dynamics -- Cusp Geometry in MHD Simulations -- The Magnetospheric Cusps: A Summary.
Keywords: Physics; Geophysics; Optics; Electrodynamics; Observations, Astronomical; Astronomy -- Observations; Space sciences; Atoms; Physics; Optics and Electrodynamics; Geophysics and Environmental Physics; Atomic, Molecular, Optical and Plasma Physics; Extraterrestrial Physics, Space Sciences; Geophysics/Geodesy.; Astronomy, Observations and Techniques; Electronic books